2017
DOI: 10.1177/1756285616684494
|View full text |Cite
|
Sign up to set email alerts
|

Diclofenac potassium for oral solution (CAMBIA®) in the acute management of a migraine attack: clinical evidence and practical experience

Abstract: Abstract:Migraine headache affects about 12% of Western populations and is the third most common disease worldwide (sixth in terms of disability). In 1993, triptans were introduced in the United States as a new treatment for managing migraine attacks, but their use is limited by lack of response and safety concerns in some patients. Treatment options for patients with migraine who fail or cannot tolerate triptans include switching to another medication or adding an adjunctive medication. Desirable characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Diclofenac is one of the most prescribed NSAIDs worldwide for the treatment of inflammatory disease and pain (33,34) and has an established role in the treatment of acute migraine. Oral diclofenac potassium in tablet, sachet or solution formulations has previously been shown to be effective, fast-acting, and welltolerated in the treatment of acute migraine attacks as an alternative to sumatriptan or other oral migraine therapies (35)(36)(37)(38)(39). Similarly, oral diclofenac epolamine is more effective than placebo in mild-to-moderate acute migraine, reducing time to attack resolution, impact on ability to work, and sensitivity to light and noise, compared with placebo (40).…”
Section: Discussionmentioning
confidence: 99%
“…Diclofenac is one of the most prescribed NSAIDs worldwide for the treatment of inflammatory disease and pain (33,34) and has an established role in the treatment of acute migraine. Oral diclofenac potassium in tablet, sachet or solution formulations has previously been shown to be effective, fast-acting, and welltolerated in the treatment of acute migraine attacks as an alternative to sumatriptan or other oral migraine therapies (35)(36)(37)(38)(39). Similarly, oral diclofenac epolamine is more effective than placebo in mild-to-moderate acute migraine, reducing time to attack resolution, impact on ability to work, and sensitivity to light and noise, compared with placebo (40).…”
Section: Discussionmentioning
confidence: 99%
“…Diclofenac can also be suggested because of its effects on substance P, β-endorphin, and NMDA receptors, and the fact that many clinical studies have demonstrated that it relieves pain. It has been shown that patients suffering from migraine who experience central sensitization with allodynia and do not achieve pain relief with other medications may benefit from the cyclooxygenase-blocking activity of diclofenac [ 86 ]. Finally, diclofenac is available for treating pain in different formulations (oral, intramuscular, topical, etc.).…”
Section: Chronic Musculoskeletal Painmentioning
confidence: 99%
“…Diclofenac in the chemical forms of acid, potassium salt or sodium salt is available on the pharmaceutical market in a large number of medicinal products in various dosage forms and with different routes of administration [ 35 , 36 ]. They include oral dosage forms (tablets, capsules), usually with modified release, rectal dosage forms, injections, products applied or sprayed on the skin, mucoadhesive dosage forms and eye drops [ 37 ].…”
Section: Adverse Effects Of Diclofenacmentioning
confidence: 99%